Research on the mechanical model and control standards for ground loss rate of shield tunnels underpassing high speed rail tunnels - Fei, Ruizhen; Peng, Limin; Zhang, Chunlei; Zhang, Peng; Zhang, Jiqing (Archives of Civil Engineering, 2026)
The analytical models for calculating the longitudinal deformation of existing high-speed railway tunnels when a shield tunnel passes beneath them mostly consider the underlying soil as a homogeneous foundation and neglect the variability of the strata. Taking into account the inherent spatial variability of the strata parameters, this study constructs a new mechanical model for the shield tunnel passing beneath existing high-speed railway tunnels, considering the influence of spatial variability in foundation stiffness, and derives the corresponding finite element solution. Through engineering case studies, the reliability of the established mechanical model for the shield tunnel passing beneath existing high-speed railway tunnels is verified. A stochastic analysis method is used to analyze the longitudinal deformation and internal forces of existing high-speed railway tunnels caused by the shield tunnel passing construction. The research results indicate: (1) For single-line shield tunnel construction, once the stratum loss rate exceeds 0.36%, the probability of exceeding the standards rapidly increases. When the loss rate reaches 0.96%, the probability of high-speed railway tunnel deformation exceeding the standards is already at 97.5%. For double-line shield tunnel construction, once the stratum loss rate exceeds 0.18%, the probability of high-speed railway tunnel performance exceeding the standards rapidly increases, and the risk of shield tunnel passing construction sharply rises. (2) The stratum loss rate during single-line shield tunnel passing beneath high-speed railway tunnels should be kept within 0.36%, while for double-line shield tunnel passing, the loss rate should be controlled within 0.18%.